Virtual reality as a tool to enhance clinical psychology students' self-knowledge and self-awareness—a proof-of-concept study - Stige, Signe Hjelen; Visted, Endre (Frontiers in Psychology, 2026)
ObjectiveExploring the use of Virtual Reality (VR) as a tool to enhance self-knowledge and self-awareness among psychology students – both conceptually and empirically.Conceptual contributionDetails are provided on the development, content, and organization of a VR-based exercise focusing on emotional recognition in oneself and others.Empirical explorationA proof-of-concept study with psychology students who had completed the VR exercise as part of their training. Forty-two out of the 94 students consented to participate and completed an online survey with open and closed questions mapping students' experiences with participating in the VR-exercise, including levels of presence and simulation sickness, and perceived benefit of the exercise in strengthening self-knowledge and self-awareness.ResultsResults indicated that the VR exercise was generally well received. Qualitative data highlighted the value of VR in simulating realistic emotional scenarios, although some participants noted difficulties recognizing emotions without contextual information. Quantitative data showed that participants who reported that they generally found it easier to recognize others' emotions also tended to find it easier to recognize both their own and others' emotions during the VR exercise. The same result was found for the general tendency to recognize one's own emotions. Importantly, higher levels of presence during the VR exercise and not general ease of recognizing emotions in others was significantly correlated with perceived benefit of the exercise. Levels of presence were not significantly impacted by prior experience with VR or discomfort, but perceived ease of recognizing emotions in others was negatively associated with presence.ConclusionThe results from this proof-of-concept study highlight the potential of using VR in clinical training to offer students immersive, controlled experiences that might foster self-knowledge and moment-to-moment self-awareness. It thus points to the need for further development and research on VR as a tool in clinical training.